THE CONFLICT RESOLUTION AMONG ETHNIC GROUPS (Study Case in South Lampung, Lampung Province) - Wawan Hernawan; Supriyanto Supriyanto; Hanindyalaila Pienrasmi (Saburai International Journal of Social Sciences and Development, 2018)
The purpose of this research is to reveal the conflict among ethnic groups that happened in South Lampung. This research used intercultural communication approach to explore about the causes of this conflict as efforts to create a solution. As an alternative approach to create the model of that solution, researchers notice about the values of local culture.This research used qualitative approach. There are two types of datas, primary and secondary. Primary data is obtained by observation and purposive interview then the secondary is from literature and government archives. There are three steps in collecting data process: orientations, exploration, and member check. Data analysis is done by data reduction which is focusing in collecting and simplify the findings, then displaying data as an arranged informations that have possibilities to make a conclusion, and the last is making conclusion and verification. These steps using interactive domain analysis in qualitative methode that comprehensive and generalize.The results showed there are horizontal conflict among ethnic groups that leads to physical abusement. This conflict is triggered by prejudice between the youngman in the village. Uncontrollable prejudice can make a bigger conflict. The local value as an alternative approach in conflict resolution between ethnics in South Lampung is Sang Bumi Ruwa Jurai which is represent in some life principal, include: 1) Julud adek, 2) Nemui nyimah, 3) nengah nyappu, 4) Sakai sambaiyan, dan 5) Titie gemattei.